Synthesis, Characterization and Biological Evaluation of Novel Methoxy Benzaldehyde Substituted Derivatives of Pyrazolopyrimidine-4-hydrazide - Mansuri, Rubeena; Badekar, Raj; Jhalora, Priyanka (Asian Journal of Chemistry, 2023)
Several novel pyrrolopyrimidine derivatives of methoxybenzaldehydes with biologically active pyrrole moieties were synthesized to investigate their antibacterial, antifungal and cytotoxic activities. Elemental analysis, UV-spectra, FT-IR, 1H NMR and 13C NMR spectra, were used to characterize the synthesized compounds. The in vitro antifungal and antibacterial activities were tested for all the synthesized compounds. Compared to the reference drugs e.g. fluconazole and streptomycin, most of the compounds tested positive for antifungal and antibacterial activity. All tested compounds demonstrated superior cytotoxic activity to the reference drug doxorubicin, with IC50 values ranging from 6.52 to 7.77 mM and comparable activity with IC50 values of 8.21 and 8.27 mM, respectively. In vitro antibacterial and antifungal activities revealed that the compouds b and e were more effective than the standard drugs streptomycin and fluconazole, respectively.